PERENCANAAN KOMUNIKASI DINAS KESEHATAN DALAM MENYUKSESKAN PROGRAM VAKSIN COVID-19 DI KOTA PALU - Rizqy Alfyaty (KINESIK, 2022)
This study aims to determine the communication planning of the Health Office in the success of the vaccine program in Palu City. The research method used is descriptive qualitative with a case study research basis. Using purposive sampling technique to determine the informants in order to obtain twelve (12) people. Data collection methods are observation, in-depth interviews and documentation with data analysis techniques through data reduction, data presentation, and verification/drawing conclusions. The results of this study indicate that the communication planning carried out by the Health Office in the success of the vaccine program in Palu City is: (1) Analyzing the problem by going directly to the community and meeting community leaders, and finding the fact that the public's lack of interest in taking vaccines because of hoax news related to vaccines; (2) Analyzing audiences and formulating communication objectives, by dividing the vaccine program targets through three stages, namely: Phase I: Health Workers; Phase II: State Civil Apparatus (government officials, TNI, and Polres); Phase III: The general public by dividing into several categories, such as people aged between 12-17 years, the elderly, pregnant women, and people with disabilities. (3) Media selection and planning for media production, the Health Service cooperates with UPTD Puskesmas, Palu City Public Relations, and other government sectors to convey information using radio, local TV, banners, billboards, websites, Instagram, Facebook as information channels and also socialize. (4) Messages delivered by the Health Service are informative and persuasive, (5) Planning communication monitoring and evaluation by conducting field visits at vaccine sites and evaluating messages on communication media